2018
DOI: 10.3389/fbioe.2018.00100
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Expression and Stability in a Large-Scale Field Study of Genetically Engineered Poplars Containing Sexual Containment Transgenes

Abstract: Genetic engineering (GE) has the potential to help meet demand for forest products and ecological services. However, high research and development costs, market restrictions, and regulatory obstacles to performing field tests have severely limited the extent and duration of field research. There is a notable paucity of field studies of flowering GE trees due to the time frame required and regulatory constraints. Here we summarize our findings from field testing over 3,300 GE poplar trees and 948 transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…Transgenic technology has been effectively used to produce poplar trees with a variety of useful traits, including herbicide resistance, biotic and abiotic tolerance, improved growth rate, higher nutrient use efficiency, and improved processing and end-use characteristics (Yang et al, 2009;Chang et al, 2018). Although many transgenic field trials have been carried out in the United States, China, and elsewhere, no transgenic trees have been commercially adopted to our knowledge (Li et al, 2016;Klocko et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic technology has been effectively used to produce poplar trees with a variety of useful traits, including herbicide resistance, biotic and abiotic tolerance, improved growth rate, higher nutrient use efficiency, and improved processing and end-use characteristics (Yang et al, 2009;Chang et al, 2018). Although many transgenic field trials have been carried out in the United States, China, and elsewhere, no transgenic trees have been commercially adopted to our knowledge (Li et al, 2016;Klocko et al, 2018).…”
mentioning
confidence: 99%
“…For most tree species, gene flow primarily occurs through seed and pollen (DiFazio et al, 2012). A number of molecular confinement strategies have been reported that may block seed and pollen-mediated transgene flow in tree species (Klocko et al, 2018). We have also recently demonstrated that an AGA-MOUS intron-driven expression of a cytotoxin gene can be used to produce flowerless tobacco (Nicotiana benthamiana), and this technique may also be effective in reducing pollen-and seed-mediated transgene flow in poplar (Li et al, 2016).…”
mentioning
confidence: 99%
“…These include genes that regulate the transition to flowering, floral organ identity as well as pollen and ovule development. Although advances in sequencing have enabled the identification of flowering gene homologs in diverse angiosperm trees, there are few cases where in planta functions have been characterized in trees ( Brunner et al, 2017 ; Klocko et al, 2018 ). This is due to the long non-flowering period that can last years to decades and that for most species, genetic transformation is a formidable hurdle.…”
Section: Current Understanding Of Reproductive Processes In Forest Trmentioning
confidence: 99%
“…Targeting such genes for manipulation can thus result in undesired vegetative effects, such as delayed bud flush, in addition to predicted effects on flowering or no effect on flowering ( Hoenicka et al, 2012 ). However, promising results have also been achieved, such as the delayed flowering without growth reduction demonstrated by overexpressing the poplar ortholog of the floral repressor SHORT VEGETATIVE PHASE (SVP) ( Klocko et al, 2018 ). Manipulation of floral organ identity genes might be less likely to have vegetative effects as these genes may show stronger conservation of reproductive-only function.…”
Section: Current Understanding Of Reproductive Processes In Forest Trmentioning
confidence: 99%
“…In Pakistan GMO food is being consumed but the labeling law is absent, whereas, equity, consistency, and fairness is the basic human right [7,8] maize, canola, cotton, and soybean are genetically engineered crops being used in different countries [9]. Other plants which are genetically engineered include poplar plant, gaining lots of interest [10]. Most recent development in biotechnology and bioengineering allows researchers to develop plant-based vaccines, plants are genetically manipulated [11] containing antigens to generate active immunity are called edible or green vaccines [12].…”
Section: Introductionmentioning
confidence: 99%